ANALISIS PENGARUH SIZE, LEVERAGE, CAPITAL INTENSITY RATIO DAN KOMISARIS INDEPENDEN TERHADAP EFFECTIVE TAX RATE (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2013-2015) - Nishfil Ayu Amaliya, 13.05.52.0055; Meita Oktaviani, Rachmawati (Students Journal of Accounting and Banking, 2017)
This study examines the effect of size, leverage, capital intensity ratio and independent commissioners towards effective tax rate. This research is conducted at Indonesia Stock Exchange by using unit of analysis of manufacturing company which have go public. Sampling method using purposive sampling with research period year 2013 until 2015. Relationship and or influence between variables explained using regression panel data analysis method with program Eviews 8. The results showed that size, capital intensity ratio and independent commissioners did not affect the effective tax rate. While leverage has a negative effect on effective tax rate.Â Keywords: Effective Tax Rate, Size, Leverage, Capital Intensity Ratio and Independent Commissioners